Become Boyan: The Arrival and Development of Baweanese in Singapore in the 19-20th Century - Mohammad Farihan Aziri; Ahmad Wahyudi (Journal of Maritime Studies and National Integration, 2019)
This article aimes to discuss the arrival and development of Baweanese people who called Boyan in Singapore in the 19-20th century. Boyan is a term for residents of Bawean Island in Singapore and Malaysia which occurs due to an error pronunciation. Baweanese people since the 19th century has visited Singapore to seek for a job. By using historical method with emphasize on the using primary sources, this research has been successfully reveal the motifs of Baweanese people migrated. In its development, Baweanese people who went to Singapore experienced a change of orientation. At the beginning of the 20th century, they preferred to settle in Singapore. The Baweanese’s migration to Singapore increased in the early 20th century after the use of steamers as their mode of transportation to go to Singapore. The emergence of mass passenger transportation routes from service agents using steam vessels has an impact on the mobility of Baweanese who migrate to Singapore. KPM's passenger agent is a catalyst for the growth and activity of Baweanese in Singapore. The aim of this stu is to explain when the Bawean people migrated to Singapore as well as the way they moved and settled in Singapore in the mid 19th century until the 20th century.